Performance outcomes at the XII International Symposium on Biomechanics and Medicine in Swimming - Hopkins, W. G.; Allen, S. V.; Vandenbogaerde, T. J. (Sportscience, 2014)
Summary of the XII International Symposium on Biomechanics and Medicine in Swimming. The BMS conference has a long history in the swimming-research community, celebrated in the opening lecture by João Paulo Vilas-Boas. The four-day program provided plenty of opportunities for research updates and the usual networking over morning and afternoon tea. Fortunately the conference program had generous breaks, which was great for catching up with old and new colleagues. There was enough new material, or new insights on traditional questions, at the BMS to make it worthwhile for attendees. This conference report is another comprehensive and informative summary of key presentation themes and outcomes. As usual, Hopkins and colleagues have cast a keen eye on performance outcomes, mechanisms and potential applications of the latest swimming research. The decision to omit discussion of abstracts dealing with lactate or VO2 measurements is understandable. Emerging and established researchers should focus on projects that could have a substantial impact on performance or provide useful insights into mechanisms, rather than addressing esoteric or academic questions.